Distinct localization of a beta-tubulin epitope in the Tetrahymena thermophila and Paramecium caudatum cortex - Libusová, Lenka; Sulimenko, Tetyana; Sulimenko, Vadym; Janisch, Roman; Hozák, Pavel; Dráber, Petr (Protoplasma, 2005)
Many of the highly organized microtubular arrangements in ciliates are located in the cortical area containing membrane vesicles and vacuoles. In Tetrahymena thermophila and Paramecium caudatum, immunofluorescence microscopy with the monoclonal antibody TU-06, directed against beta-tubulin, revealed distinct staining of this cortical region alone, while the cilia and other microtubular structures were unstained. The specificity of the antibody was confirmed by immunoblotting and by preabsorption of the antibody with purified tubulin. Double-label immunofluorescence with antibodies against gamma-tubulin, detyrosinated alpha-tubulin, and centrin showed that the TU-06 epitope is localized outside the basal body region. This was also confirmed by immunogold electron microscopy of thin sections. Proteolytic digestion of porcine brain beta-tubulin combined with a peptide scan of immobilized, overlapping peptides disclosed that the epitope was in the beta-tubulin region beta81-95, a region which is phylogenetically highly conserved. As known posttranslational modifications of beta-tubulin are located outside this area, the observed staining pattern cannot be interpreted as evidence of subcellular sequestration of modified tubulin. The limited distribution of the epitope could rather reflect the dependence of TU-06 epitope exposition on conformations of tubulin molecules in microtubule arrangements or on differential masking by interacting proteins.
Keywords: Tubulin; Epitopes; financování organizované; Animals; 3T3 Cells; Paramecium; Mice; myši; Immunoblotting; Financing, Organized; tubulin; Tetrahymena thermophila; Epitope Mapping; buňky 3T3; imunoblotting; epitopy; zvířata; buněčná membrána; mapování epitopu; Cell Membrane